PENGARUH PERBEDAAN SUHU EKSTRAKSI TERHADAP KEKUATAN GEL, VISKOSITAS, RENDEMEN DAN pH GELATIN KULIT BABI - Gerungan, Deysi; Sompie, M.; Soputan, J.M; Mirah, A.Dp. (Universitas Sam Ratulangi, 2019)
THE EFFECT OF EXTRACTION TEMPERATURE DIFFERENCES ON GEL STRENGTH, VISCOCITY, YIELD AND pH OF PIGSKIN GELATIN. This study aims to determine the influence of differences in extraction temperature on gel strength, viscosity, yield and pH value of pigskin. This study used a Completely Randomized Design (CRD) with an extraction temperature treatment (40℃, 50℃, 60℃ and 70℃), each treatment repeated four times. The results showed that the differences in gelatin extraction temperature of pigskin had a significantly different effect (P <0.05) on gel strength and yield of pigskin gelatin, but had no significant effect (P> 0.05) on viscosity and pH value. Based on the results, it can be concluded that the gelatin from pigskin with an extraction temperature of 70℃ had a optimal physical characteristics.Keywords : Extraction, Gelatin, Pigskin